Kesetaraan Gender Dalam Perspektif Pesantren Al-Zaitun - Nisa, Haliatun; Fajrussalam, Hisny; Nurlena, Regina; Nurhaliza, Ridha (Peneliti.net, 2024)
This paper explains the Deviation of Ma'had Al-Zaytun's Teachings Against Islamic Law where the activity was located in a ma'had or hut in Indramayu, Central Java. On the leadership of Prof. Dr. KH. Abdusallam Rasyidi Panji Gumilang has recently attracted a lot of controversy because the teachings applied in the education center are contrary to Islamic laws or teachings juxtaposed with a gender equality perspective, such as the spaced prayer shaf and the mixing of male and female and female sermons during Friday prayers, the research method used is the literature method or, where researchers rely on different literature to Get research information and use a qualitative approach, because the information produced is in the form of words or descriptions.